Generalized multiplicative bases for one-sided bimodule problems - Babych, V.; Golovashchuk, N.; Ovsienko, S. (Algebra and Discrete Mathematics, 2011)
We consider a class of normal bimodule problems satisfying some structure, triangularity and finiteness conditions. For a bimodule problem from this class we construct explicitly an analogue of multiplicative basis which we call quasi multiplicative.